Performance of floating solar panel in improving temperature of solar panel - Mohd. Helmi Mazlan, 1995-, author; Jasrul Jamani Jamian, 1985-, supervisor; Fakulti Kejuruteraan Elektrik (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik)) - Universiti Teknologi Malaysia, 2018